ANÁLISIS DE FACTIBILIDAD DE LA INCORPORACIÓN DE SISTEMAS DE CARGA LENTA PARA VEHÍCULOS ELÉCTRICOS EN REDES DE DISTRIBUCIÓN DE USO RESIDENCIAL EN LA PARROQUIA SAN CAMILO - CHULCO SIGCHA, LUIS JONATHAN (2025)
This project analyzes the feasibility of incorporating slow charging systems for EVs into residential distribution networks in the San Camilo Parish, Los Ríos Province. Due to the growth of electric mobility and the limited charging infrastructure in the country, the impact of these systems on energy demand and grid stability is being evaluated